A population-based study on the effect of a routine second-look resection on survival in primary stage T1 bladder cancer. (4th March 2021) - Bobjer, Johannes; Hagberg, Oskar; Aljabery, Firas; Gårdmark, Truls; Jahnson, Staffan; Jerlström, Tomas; Sherif, Amir; Ströck, Viveka; Häggström, Christel; Holmberg, Lars; Liedberg, Fredrik
Abstract: Objective: To assess the value of second-look resection (SLR) in stage T1 bladder cancer (BCa) with respect to progression-free survival (PFS), and also the secondary outcomes recurrence-free survival (RFS), bladder-cancer-specific survival (CSS), and cystectomy-free survival (CFS). Patients and methods: The study included 2456 patients diagnosed with stage T1 BCa 2004–2009 with 5-yr follow-up registration in the nationwide Bladder Cancer Data Base Sweden (BladderBaSe). PFS, RFS, CSS, and CFS were evaluated in stage T1 BCa patients with or without routine SLR, using univariate and multivariable Cox regression with adjustment for multiple confounders (age, gender, tumour grade, intravesical treatment, hospital volume, comorbidity, and educational level). Results: SLR was performed in 642 (26%) individuals, and more frequently on patients who were aged < 75 yr, had grade 3 tumours, and had less comorbidity. There was no association between SLR and PFS (hazard ratio [HR] 1.1, confidence interval [CI] 0.85–1.3), RFS (HR 1.0, CI 0.90–1.2), CFS (HR 1.2, CI 0.95–1.5) or CSS (HR 1.1, CI 0.89–1.4). Conclusions: We found similar survival outcomes in patients with and patients without SLR, but our study is likely affected by selection mechanisms. A randomised study defining the role of SLR in stage T1 BCa would be highly relevant to guide current praxis.